Peran Perawat dalam Penanganan Syok Anafilaksis: Studi Observasional di RSUD Tipe B - Pannyiwi, Rahmat; Lestari, Ima Mustika Tri; Nursinah, Nursinah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Anaphylactic shock is a severe allergic reaction that can be fatal if not treated promptly. Nurses, as frontline healthcare workers, play a crucial role in early detection and rapid intervention in this condition. Objective: To determine the role of nurses in managing anaphylactic shock in the emergency department (ED) of a Type B Regional General Hospital. Methods: This was an observational study using a quantitative descriptive approach. Data were obtained through direct observation of nurses' actions using a standard operating procedure (SOP)-based checklist and semi-structured interviews. The sample consisted of 30 nurses working in the ED. Results: 76.7% of nurses demonstrated good skills in the initial assessment, but only 60% administered epinephrine injections according to procedure. 83.3% of nurses were able to monitor vital signs regularly and document them appropriately. Conclusion: The role of nurses in managing anaphylactic shock in the ED of a Type B Regional General Hospital is considered adequate, but skills in administering epinephrine and follow-up care are still needed.